Android-Based Fashion Stylist and Event Outfit Application - Heri Purwanto; Mohamad Gifahri Addiansyah; Fauzi Ramdani; Akbar Al Ghifari (International Journal of Engineering, Science and Information Technology, 2022)
Fashion or style of dress as a form of self-expression, is closely related to the way people communicate values, personality, status, identity, and feelings to others. Adolescence is a period in which a person experiences considerable physical development where they are more sensitive to their appearance, today's teenagers enjoy trends that are appropriate for their time and strive to become a well-known trendsetter among their circles. The purpose of this research is to help the public, especially teenagers, to have knowledge about modern fashion trends in Indonesia. The application development method used is the agile method and the data collection techniques used are observation, interviews and literature study. The modeling language used is UML including Use Case Diagrams, Use Case Scenarios, Activity Diagrams, Class Diagrams and the programming languages that will be used are Java, Android Studio, then SQLite as a place for database design. The results of this study aim to develop an Android-based fashion stylist and event outfit application as well as assist in simplifying the process of choosing clothes that are suitable for use and can save time in choosing clothing ideas of interest so as to provide an overview of modern fashion in Indonesia and can be worn in accordance to the event Outfit to be attended, and according to the number of events to be held.